Postoperative Lumbar Fusion Bone Morphogenic Protein–Related Epidural Cyst Formation - Abel, F.; Tan, E.T.; Sneag, D.B.; Lebl, D.R.; Chazen, J.L. (American Journal of Neuroradiology, 2023)
SUMMARY: Bone morphogenetic protein is broadly used in spinal surgery to enhance fusion rates. Several complications have been associated with the use of bone morphogenetic protein, including postoperative radiculitis and pronounced bone resorption/osteolysis. Bone morphogenetic protein–related epidural cyst formation may represent another complication that has not been described aside from limited case reports. In this case series, we retrospectively reviewed imaging and clinical findings of 16 patients with epidural cysts on postoperative MR imaging following lumbar fusion. In 8 patients, mass effect on the thecal sac or lumbar nerve roots was noted. Of these, 6 patients developed new postoperative lumbosacral radiculopathy. During the study period, most patients were managed conservatively, and 1 patient required revision surgery with cyst resection. Concurrent imaging findings included reactive endplate edema and vertebral bone resorption/osteolysis. Epidural cysts had characteristic findings on MR imaging in this case series and may represent an important postoperative complication in patients following bone morphogenetic protein–augmented lumbar fusion.ALIFanterior lumbar interbody fusionBMPbone morphogenetic proteinLLIF/XLIFlateral/extreme lateral lumbar interbody fusionL-spinelumbar spinePLIFposterior lumbar interbody fusionPLLposterior longitudinal ligamentrhBMP-2recombinant bone morphogenetic protein-2TLIFtransforaminal lumbar interbody fusion